Impact of Taxes and Fees on the Productivity of the Palestinian Industrial Sector - Jawad, Yousef Abdel; Zabada, Shaker (International Journal of Economics and Financial Issues, 2019)
The study aimed to determine the effect of taxes and fees on the productivity of the industrial sector in Palestinian case, also in the details at the level of economic activity. To achieve the objectives of this study, the descriptive and quantitative methodology was used. Based on the data of the economic survey series cross sectional data in 2015 was used and, provided by the Palestinian Central Bureau of Statistics (PCBS), the Ordinary Least Squares Method (OLS) was used in regression analysis. The study found that the effect of taxes on the productivity of the industrial sector is small in general and varies according to the nature of the economic activity. This is different from the expectation that the effect of taxes will be negative. This is mainly because the high degree of tax evasion in Palestine while it does not constitute as a burden in other countries. Keywords: Productivity, Taxes, Fees, Industrial sector. JEL Classifications: D2, L2, O4, G38 DOI: https://doi.org/10.32479/ijefi.7559